A kisebbségi iskolaügy Balázs Ferenc tevékenysége alapján 1938–1944 között - Niklai, Patrícia Dominika (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2021)
Ferenc Balázs served as a rapporteur of minority education directly under the administration of the Ministry of Religion and Education between 1938 and 1944. Almost the whole area of Transdanubia (so-called ’Dunántúl’) belonged to his competence. His task was to observe the introduction of the unified education system, then to monitor the transition to full native language education from 1941. There have been many obstacles to both of the systems. In addition to these, he had to take into account the activity of the Volksbund, which acted decisively; Balázs was able to handle these situations objectively based on the documemted events. He examined hundreds of schools, the results were regularly reported to the Ministry. He did not only deal with the effectiveness of the national education system in a narrow sense, but also with issues related to public education in general: the condition of school buildings, deficiencies in equipment, the social and health status of children, the training of teachers. Moreover he has been involved in major events affecting the day-to-day running of schools, such as secret ballots prior to the introduction of full native language education, inspection of the language skills of teachers, supervising the preparation of curriculum and syllabus, but for example, he also translated the text of the prayer used in teaching to German.